A Section Containing Selected Hadiths and Benefits from The Hearings of Ibn al-Shaykha (d. 799 AH) Takhrij by: Al-Hafiz al-Iraqi al-Hafiz. Study and Verification: جُزْءٌ فِيهِ أَحَادِيثُ عَوَالٍ وَفَوَائِدُ مُنْتَقَاةٌ مِنْ سَمَاعَاتِ الشَّيْخِ الْمُسْنِدِ أَبِي الْفَرَجِ عَبْدِ الرَّحْمَنِ بْنِ أَحْمَدَ بْنِ الْمُبَارَكِ الْغَزِّيِّ الشَّافِعِيِّ، الشَّهِيرِ بِابْنِ الشَّيْخَةِ، (المتوفى: 799هـ)، تَخْرِيجُ: الْحَافِظِ وَلِيِّ الدِّينِ أَبِي زُرْعَةَ أَحْمَدَ بْنِ الْحَافِظِ أَبِي الْفَضْلِ عَبْ - AbdelRahman ElSayed ElSayed AbdelGhaffar Balah (PT. Student Rihlah Indonesia, 2026)
This research aims to investigate this precious hadith part, and its material of hadiths, narrations, and poems. In it, Abd al-Rahman bin Ahmad Ibn al-Sheikha, may God have mercy on him, the author of the part collected a number of hadiths, narrations, and poems that differ from his sheikhs, and are not specialized in a specific topic or issue. The part included and contained twenty-two hadiths, influences, and benefits. In his research, the researcher followed the inductive, descriptive, analytical, and critical approach, due to its suitability for this type of studies.